Epidemiological, molecular characterization and antibiotic resistance of Salmonella enterica serovars isolated from chicken farms in Egypt. Issue 1 (December 2017) - El-Sharkawy, Hanem; Tahoun, Amin; El-Gohary, Abd; El-Abasy, Moshira; El-Khayat, Fares; Gillespie, Trudi; Kitade, Yukio; Hafez, Hafez; Neubauer, Heinrich; El-Adawy, Hosny
Abstract Background Salmonella is one of major causes of foodborne outbreaks globally. This study was conducted to estimate the prevalence, typing and antibiotic susceptibilities ofSalmonella enterica serovars isolated from 41 broiler chicken farms located in Kafr El-Sheikh Province in Northern Egypt during 2014–2015. The clinical signs and mortalities were observed. Results In total 615 clinical samples were collected from broiler flocks from different organs (liver, intestinal content and gall bladder).Salmonella infection was identified in 17 (41%) broiler chicken flocks and 67Salmonella isolates were collected. Recovered isolates were serotyped as 58 (86.6%)S. enterica serovar Typhimurium, 6 (9%)S. enterica serovar Enteritidis and 3 (4.5%) were non-typable. The significant high mortality rate was observed only in 1-week-old chicks.sop E gene was detected in 92.5% of the isolates which indicating their ability to infect humans. AllS. enterica serovar Enteritidis isolates were susceptible to all tested antimicrobials. The phenotypically resistantS. enterica serovar Typhimurium isolates against ampicillin, tetracycline, sulphamethoxazole and chloramphenicol were harbouringBla TEM, (tet A andtet C), (sul 1 andsul 3) and (cat 1 andflo R), respectively. The sensitivity rate ofS. enterica serovar Typhimurium to gentamycin, trimethoprim/sulphamethoxazole and streptomycin were 100, 94.8, 89.7%, respectively. The silent streptomycin antimicrobial cassettes were detected in allSalmonella serovars. A class one integron (dfr A12, orf F andaad A2) was identified in three ofS. enterica serovar Typhimurium strains. Conclusions To the best of our knowledge, this study considered first report discussing the prevalence, genotyping, antibiotic susceptibility and public health significance ofS. enterica serovars in broilers farms of different ages in Delta Egypt. Further studies are mandatory to verify the location of some resistance genes that are within or associated with the class one integron.